La politique canadienne d’immigration - Crépeau, François (Assurances, 1987)
The topic of this article appears to have little to do with insurance. But does immigration not represent, to a large extent, the growth and diversity of Canada's population? ln years gone by, Canada would very often welcome anyone who was willing to come to live here, regardless of how they would have to live once here. Then an immigration policy gradually began to take shape and selection criteria became increasingly demanding. Today, the door is no longer open to anyone. lmpressed with the remarkable precision with which Mr. Crépeau discusses immigration, the least we could do was publish a revised version of the conclusion of the author's study. After all, is immigration not the population of tomorrow? ln this respect, the topic is linked to insurance, in all its forms.